Extraer estándares y criterios de hoteles hospitalarios con un enfoque de diseño hospitalario especializado - Shirvani, Mohammad; Heydarian, Khatereh (Innovaciencia, 2020)
Background and Aim: Hospital design is based on the theoretical foundations of architecture and careful planning based on activities, equipment, standards and specific relationships between spaces. Applying the right standards and relationships between functions has a direct impact on the proper context of treatment. According to what has been said, the purpose of this study is to extract the standards and criteria of the hospital hotel with a specialized hospital design approach. Materials and Methods: The present study is a quantitative-qualitative method and based on this, first the qualitative evaluation of hospital environments in Kermanshah and then in the next stage, the obtained and presented standards have been proved. In order to evaluate the quality and evaluate the compatibility of the use of the standard environment, a semi-structured individual interview with hospital design specialists and researchers in this field and qualitative analysis of texts were used. The data obtained from the interviews were analyzed by coding method and in the next step, using the confirmatory factor analysis and laser software, the presented indicators were proved. Results and Results: In establishing hoteling standards in a specialized hospital, in addition to designing the initial physical spaces appropriate to the type of disease, three main questions were: Reasons for using the hospital hotel standard, the fit of the standards with the patient’s needs and what these standards are. From the present study, we can point to the required standards in the field of hospital hotels with the approach of a specialized hospital with four basic indicators such as building and equipment, welfare services, human factors and functional factors. These are among the basic and emphasized standards that have been neglected.